Gerakan Literasi Sekolah Di SDN 190 Pekanbaru - Ningsih, Annisa Darma; Dafit, Febrina (Peneliti.net, 2023)
GLS is a social movement that is planned and involves all components of education so that the love of reading is realized and the character of students is to get used to life by reading first. Literacy activities cannot be separated from schools, this is because schools have an important role in carrying out literacy activities. Literacy can be a good tool as a medium to get information which, when implemented properly, will also have a good impact on students. The purpose of this study is to describe how the GLS is implemented at SDN 190 Pekanbaru. This study uses a descriptive qualitative method where the data obtained will be translated into a sentence that behaves descriptively. Data collection techniques in this study were observation, interviews and documentation. Based on the data obtained, it can be seen that in general the implementation of the GLS has been going well which has been carried out through several stages, namely planning, implementation and evaluation. Some of the obstacles that hinder GLS at SDN 190 Pekanbaru are the lack of facilities such as books and libraries and there are still students who don't care about GLS activities.